Effects of Eco-Enzyme Concentrations and Growing Media on the Growth Performance of Pakcoy Microgreens - Ni Kadek Desy Andya Dewi; Adellia Novianti; I Gusti Bagus Udayana; I Nengah Muliarta; Ni Luh Putu Sulis Dewi Damayanti (SEAS (Sustainable Environment Agricultural Science), 2026)
Microgreens are young vegetable seedlings valued for their high nutritional content and rapid growth cycle. Pakcoy microgreens (Brassica rapa chinensis L.) have strong potential for sustainable urban agriculture. This study aimed to evaluate the effects of different eco-enzyme concentrations and growing media on the growth performance of pakcoy microgreens. The experiment was conducted using a factorial completely randomized design with two factors: eco-enzyme concentration and growing media type. Several growth parameters were observed, including plant height, number of leaves, fresh weight, and overall growth vigor. The results showed that both eco-enzyme concentration and growing media not  significantly influenced the growth of pakcoy microgreens. Higher eco-enzyme concentrations generally promoted better vegetative growth, particularly when combined with suitable growing media. The interaction between eco-enzyme application and growing media played an important role in optimizing microgreen growth performance. These findings indicate that eco-enzyme can be utilized as an environmentally friendly input to enhance pakcoy microgreen production. The use of appropriate growing media further improves growth outcomes, supporting sustainable and efficient microgreen cultivation systems. This study provides practical insights for small-scale growers and urban farmers seeking to improve microgreen productivity using eco-friendly alternatives.